Variationalism and Individualism: Beyond the Modern Synthesis - Walsh, Denis M. (Philosophy, theology and the sciences, 2020)
Increasingly, it is becoming apparent that the processes that occur within individuals are crucially involved in each of the component processes of evolution: development, inheritance, innovation, and adaptive change. Any comprehensive evolutionary theory must reserve a place for the ways in which the properties that make organisms organisms - their self-regulating, self-synthesising, purposiveness - figure in the evolution of organismal fit and diversity.